Chinese newspaper coverage of genetically modified organisms - Du Li; Rachul Christen (BMC, 2012)
Abstract Background Debates persist around the world over the development and use of genetically modified organisms (GMO). News media has been shown to both reflect and influence public perceptions of health and science related debates, as well as policy development. To better understand the news coverage of GMOs in China, we analyzed the content of articles in two Chinese newspapers that relate to the development and promotion of genetically modified technologies and GMOs. Methods Searching in the Chinese National Knowledge Infrastructure Core Newspaper Database (CNKI-CND), we collected 77 articles, including news reports, comments and notes, published between January 2002 and August 2011 in two of the major Chinese newspapers: People's Daily and Guangming Daily. We examined articles for perspectives that were discussed and/or mentioned regarding GMOs, the risks and benefits of GMOs, and the tone of news articles. Results The newspaper articles reported on 29 different kinds of GMOs. Compared with the possible risks, the benefits of GMOs were much more frequently discussed in the articles. 48.1% of articles were largely supportive of the GM technology research and development programs and the adoption of GM cottons, while 51.9% of articles were neutral on the subject of GMOs. Risks associated with GMOs were mentioned in the newspaper articles, but none of the articles expressed negative tones in regards to GMOs. Conclusion This study demonstrates that the Chinese print media is largely supportive of GMOs. It also indicates that the print media describes the Chinese government as actively pursuing national GMO research and development programs and the promotion of GM cotton usage. So far, discussion of the risks associated with GMOs is minimal in the news reports. The media, scientists, and the government should work together to ensure that science communication is accurate and balanced.